2019
DOI: 10.1111/1348-0421.12730
|View full text |Cite
|
Sign up to set email alerts
|

8‐Methoxypsoralen protects bovine mammary epithelial cells against lipopolysaccharide‐induced inflammatory injury via suppressing JAK/STAT and NF‐κB pathway

Abstract: Bovine mastitis is the most common disease in dairy cattle. Bacterial infections are the main cause of mastitis. Lipopolysaccharide (LPS), a major structural component of the cell wall of Escherichia coli, is a good inducer used to replicate inflammation models. 8‐Methoxypsoralen (8‐MOP), a formerly considered photosensitizing agent, has been used in immunotherapy. This study investigated the protective effects of 8‐MOP on LPS‐induced inflammatory injury in bovine mammary epithelial cells (BMECs). LPS treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Also phenolic acids have been already studied for their anti-inflammatory activity, and compounds such as chlorogenic acids, ferulic acid and quinic acid, characterized in COME, have been reported to attenuate the production of pro-inflammatory cytokines in murine cells by down regulating the NF-κB pathway [59][60][61]. Among the other compounds identified in COME, the two coumarins umbelliferone and methoxsalen have been reported to suppress the expression of NF-κB in animal models [62,63], while peonidin-3-glucoside to reduce the metastasis of lung cancer cells by acting via different mechanisms, among which the blocking of AP-1 activation [64]. Overall, these constituents could also contribute to the observed anti-inflammatory and cytotoxic activities of COME.…”
Section: Discussionmentioning
confidence: 99%
“…Also phenolic acids have been already studied for their anti-inflammatory activity, and compounds such as chlorogenic acids, ferulic acid and quinic acid, characterized in COME, have been reported to attenuate the production of pro-inflammatory cytokines in murine cells by down regulating the NF-κB pathway [59][60][61]. Among the other compounds identified in COME, the two coumarins umbelliferone and methoxsalen have been reported to suppress the expression of NF-κB in animal models [62,63], while peonidin-3-glucoside to reduce the metastasis of lung cancer cells by acting via different mechanisms, among which the blocking of AP-1 activation [64]. Overall, these constituents could also contribute to the observed anti-inflammatory and cytotoxic activities of COME.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK-STAT pathway, and specially STAT5 action, is central for milk synthesis by mammary cells (Reichenstein et al 2011). Recent studies have also revealed that the JAK-STAT pathway is closely related to cellular immunity (Stabile et al 2018;Li et al 2019). When STAT5 was abnormally activated, it regulated the expression level of BCL-2 to change cell cycle progression and block apoptosis in several cancer cell lines (Xi et al 2003;Li et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It not only controls milk synthesis (Campo Verde Arbocco et al 2017), but also participates in the regulation of the immune response (Villarino et al 2017). Li reported that JAK/STAT pathway could be suppressed by 8-methoxypsoralen to protect bovine mammary epithelial cells against lipopolysaccharide-induced inflammatory injury (Li et al 2019). Usman et al indicated that mastitis in Chinese Holstein cows was associated with down-regulation of the JAK-STAT pathway genes JAK2, STAT5A and STAT5B (Usman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [113] H2S Block TLR4, ROS, NF-κB Garcia et al [125] Citrus oils Antibacterial Down-regulate TLR2, NFKBIA, IL8, TNF-α Wang et al [78] Morin Anti-inflammatory Inhibit IL-6, TNF-α, IL-1β, suppress NF-κB phosphorylation Li et al [126] 8-Methoxypsoralen Anti-inflammatory Inhibit IL-6, TNF-α, IL-8, IL-1β, suppress NF-κB phosphorylation Chen et al [36] Nuciferine Anti-inflammatory Inhibit TLR4, TNF-α, IL-1β, suppress NF-κB phosphorylation Yang et al [127] Oxymatrine Anti-inflammatory Suppress NF-κB phosphorylation Ershun et al [128] Cepharanthine Anti-inflammatory Inhibit IL6, TNF-α, IL-1β, suppress NF-κB phosphorylation Su et al [129] Rutin Decrease level of IL-1β, IL-6, and TNF-α, suppress NF-κB phosphorylation Liu et al [112] Sodium houttuyfonate Antinflammatory Inhibit NF-κB phosphorylation Li et al [130] Emodin ameliorates Anti-inflammatory, antibacterial Decrease level of IL-1β, IL-6, and TNF-α, suppress NF-κB phosphorylation Hu et al [42] Cynatratoside-C from Cynanchum atratum Anti-inflammatory Suppress TLR4, inhibit NF-κB phosphorylation He et al [131] Docosahexaenoic acid Anti-inflammatory Decrease level of IL-1β, IL-6, and TNF-α, suppress NF-κB phosphorylation He et al [132] Baicalein Anti-inflammatory Suppress TLR4, inhibit NF-κB phosphorylation…”
Section: Agent Function Targetsmentioning
confidence: 99%